Language and power - Fairclough, Norman (Routledge, 2015)
Language and Power is widely recognised both as a classic and an essential introductory textbook to the field of Critical Discourse Analysis. It focusses on how language functions in maintaining and changing power relations in modern society, the ways of analysing language which can reveal these processes and how people can become more conscious of them, as well as, more able to resist and change them.